Foreign Language Classroom Anxiety across STEM and Social Science Students: Evidence from Undergraduate EFL Learners - Badriyah Ulfah (Fakultas Sastra - Universitas Muslim Indonesia, 2026)
Foreign language classroom anxiety (FLCA) remains an important affective issue in English as a foreign language (EFL) learning, particularly in higher education contexts where students are expected to use English for academic and professional purposes. However, limited attention has been given to whether students from different academic disciplines experience different levels of FLCA. This study investigated the overall level of FLCA among Indonesian undergraduate EFL learners and examined whether there was a significant difference between STEM and Social Science students. Using a quantitative descriptive-comparative design, data were collected from 254 undergraduate students through a 20-item FLCA questionnaire. The overall FLCA score was calculated as a single construct, and the data were analyzed using descriptive statistics, anxiety-level categorization, Welch’s t-test, and Cohen’s d. The findings showed that students experienced a moderate level of FLCA (M = 3.02, SD = 0.74). Most students were categorized as having moderate anxiety (66.9%), followed by low anxiety (16.9%) and high anxiety (16.1%). The comparison between disciplinary groups revealed that Social Science students reported higher FLCA (M = 3.20, SD = 0.65) than STEM students (M = 2.84, SD = 0.79). Welch’s t-test confirmed a significant difference between the two groups, t (240.70) = 4.03, p < .001, with a small-to-moderate effect size (d = 0.51). These findings suggest that disciplinary background may shape students’ anxiety in English classroom learning and highlight the need for more discipline-sensitive EFL instruction in Indonesian higher education.